The corporate real effects of CIP deviations - Filippo Ippolito; José-Luis Peydró; Artashes Karapetyan; Ragnar Enger Juelsrud; Olav Syrstad (Norges Bank, 2024)
We show corporate real effects from Covered Interest Parity (CIP) deviations, exploiting administrative data from Norway as well as CIP deviation shocks. Banks with access to U.S. money markets strongly increase short-term USD funding in response to CIP deviations. This, in turn, leads to higher credit to non-financial firms. The increase in credit is robust to firm-time fixed effects, suggesting that it is supply-driven. Moreover, firms receiving additional credit also pay lower interest rates. These loan-level results translate into an increase in firm-level bank debt and total debt. However, corporate real effects are weaker. Despite strong effects on corporate sales (firm output), affected firms (i.e., with higher credit availability) increase their fixed assets completely driven by an increase in financial fixed assets, not through investment in real assets. Further, more affected firms pay out more dividends to shareholders.
hdl:11250/3172093
Keywords: G21; F31; F65; E4; 330; CIP deviations; bank lending channel; global banks